Kajian Teknis Pembangkit Listrik Hybrid (Pv & Wtg) Pada Base Transceiver Station (Bts) Di Pulau Karimunjawa - Safrizal Safrizal (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2020)
Energy crisis of the world's oil and environmental pollution caused by burning fossil fuels to produce electrical energy, global warming has an impact on a very alarming level. The completion of the impact of global warming, which is one of them by reducing the energy use of fossil fuel-based electricity and alternative energy utilization (renewable energy) around it. Supplying electrical energy for operating the BTS (Base Transceiver Station), which is sourced solar power plant (PLTS) or Solar cells, Wind Power Generation (Wind turbine) and Hybrid Power Plant (Solar Cell integration with Wind Turbine) environmentally friendly (green energy ) capable of replacing conventional electrical energy either fossil fuel-based, derived from the power provider (PLN) or Genset, as well as capable of reducing levels of CO2 in the air. In this paper a discussion of solar panel power supply or 71.7% (93.46 kWh) of electricity consumption overall BTS 130.35 Kwh / day, with 72 panels and Wind turbine supply 28.3%. or 37 kWh / day consisting of 4 units of wind turbines x 545 Wp x 17 hours = 37,060 Wh / day, as well as reductions, CO2 emissions of 0.719 kg / kWh x 130.35 = 93.721 Kg / day.